An atypical presentation of primary central nervous system lymphoma: A case report. Issue 38 (18th September 2020) - Yuen, Carlen A.; Mastrianni, James; Ali, Saad; Pytel, Peter; Park, Deric M.; Rezania, Kourosh
Abstract: Rationale: Primary central nervous system lymphoma ( PCNSL) involving the choroid plexus is exceedingly rare. The differential diagnosis for choroid plexus enhancing lesions in addition to lymphoma includes infections, sarcoidosis, tuberculosis, papilloma, meningioma, subependymoma, and metastatic lesions. Patient concerns: A 71-year-old man presented with 3 days of episodic memory loss and gait disturbance. Brain magnetic resonance imaging showed homogenously enhancing lesions with mildly restricted diffusion and T2 hypointensity in the lateral ventricles, as well as T2 hyperintensity and enhancement in the right hippocampus. His episodic memory loss was thought to be secondary to subclinical focal seizures, supported by EEG revealing right temporal lobe epileptiform discharges. Diagnoses: Large B-cell lymphoma, nongerminal center type was revealed on pathological examination. Interventions: Stereotactic biopsy of his right thalamic lesion was performed. Outcomes: The patient underwent induction therapy with high-dose methotrexate, temozolomide, and rituximab, which resulted in complete resolution of the enhancing lesions. He then underwent conditioning chemotherapy with carmustine and thiotepa, followed by autologous stem cell transplantation. His PCNSL remains in remission 42 weeks after the onset of symptoms. Lessons: We report a patient with multifocal PCNSL involving the choroid plexus, who presented with abnormal gait and episodic confusion and memory loss. PCNSL should be considered in the differential diagnosis of acute encephalopathy among immunocompetent older individuals who have choroid plexus enhancing lesions.